Cross-sectional survey to assess the knowledge, attitude and practice regarding adverse drug reactions of students of a private university - Islam, Tarikul (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Pharmacy, 2021.